Lessons in Perception The Avant-Garde Filmmaker as Practical Psychologist - Taberham, Paul (Berghahn Books, 2018)
Lessons in Perception seeks to clarify notoriously elusive themes of the avant-garde with the use of existing research from the field of psychology. There is a long-standing history of reference to psychological concepts in relation to avant-garde film, such as its unique relationship to memory, visual perception, narrative comprehension, and synesthesia. Yet direct analysis of these topics in light of existing psychological research remains largely unexplored until now. More broadly, the aim of the book is to frame avant-garde filmmaking practice as a form of "practical psychology." In doing so, two principal arguments are proposed: first, that many avant-garde filmmakers draw creative inspiration from their own cognitive and perceptual capacities, and touch on topics explored by actual psychologists; secondly, that as practical psychologists, avant-garde filmmakers provide "lessons in perception" that offer psychological experiences that are largely unrehearsed in commercial cinema.